Pengembangan Sistem Informasi Penggajian Pada Tugu Hotel Lombok Menggunakan Metode Rational Unified Process - Anas Zulbichaq; Yusi Tyroni Mursityo; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The employee payroll calculation of Tugu Hotel Lombok is still less efficient and effefctive. Efficiency and effectiveness improvement could be achieved with presence an information system which can help out calculation process. Research on development of payroll information system is to produce an prototype information system that could give efficiency improvement and reduce human error on employee payroll calculation. Res analysis done using unstructure interview method. After did res analysis and literature study, do development process use RUP method. Inception phase will be modeled the as-is business process and to-be business process, feature, functional and non-functional requirement. In elaboration phase deliver UML diagram like use case diagram as a reference to modeling some diagram else like activity diagram and sequence diagram. The result of analysis class diagram as reference to physical data modeling. Analysis and designing using object oriented method (OOA/D). in construction phase is developing system using OOP method approach. After develop the system according by design before, next step is carried out test the system. Testing use database testing, validation testing, and compatibility testing methods. Database testing done on construction phase. In transition phase is done compatibility testing and validation testing. Database testing and validation testing is done on main features of this system, and compatibility testing is done to find out feasibility system in different environment. The test result claim that information system run according by requirements and could used easily by the users.